Simulation of Start-up of Anode Gas Recycle SOFC System Using Catalytic Combustion Method. (2nd June 2015) - Baba, Soumei; Kobayashi, Nariyoshi; Takahashi, Sanyo; Hirano, Satoshi
Abstract : Solid oxide fuel cells (SOFCs) are the most efficient known converters of chemical to electrical energy, and simple, compact SOFC designs are actively sought. We simulated an anode gas recycle SOFC system using a catalytic combustion method during transient operations (i.e., startup and shutdown). In this system, methane fuel conversion is enabled by oxidation air that is injected by a catalytic combustion reaction in the combustor section located upstream of the pre-reformer section. The effects of the operation conditions (i.e., the stack temperature, air-to-methane feed ratio, fuel utilization, and recirculation ratio) on system performance were clarified via chemical equilibrium calculations. From the results of this simulation, we determined the operational procedures and system configurations corresponding to the stack temperature and load conditions.